Financial Performance of State Banks Indonesia - Desi Nazarulita; Nizwan Zukhri; Rini Yayuk Proyati (Fakultas Ekonomi Universitas Bangka Belitung, 2021)
Financial institutions have a very important role for Indonesian economy. This study aims to analyze the effect of capital adequacy (CAR), liquidity (LDR), credit risk (NPL), operational efficiency (BOPO) on profitability (ROA). The analysis technique using panel data regression such as: common effect models, fixed effect models, random effects models. The data sourced from four state-owned banks listed on The Indonesian Stock Exchange during 2010-2018. The analysis shows that only CAR and BOPO variables have a significant (negative) effect on ROA. Meanwhile, LDR and NPL, did not have a significant effect. Further research is suggested added others variables that affected to profitabilities, increase the period of the research, hopefully, it will improve data accuration.